The presence of neighbors influences defense against predators in a cooperatively breeding cichlid. (24th January 2014) - Hellmann, Jennifer K.; Hamilton, Ian M.
Lay Summary: Individuals adjust their response to predators based on the presence or absence of neighboring groups. Within groups of fish, we found that subordinate helpers, but not dominant breeders, increased their aggression toward a predator when neighboring groups were present. Although individual behavior is usually studied in a group context, we demonstrate that the larger social context needs to be considered because neighboring groups may offer important reproductive opportunities or alter social dynamics of nearby groups. Abstract : Although behavior is often examined in a dyadic or group context, behavioral interactions are also influenced by the broader social context. Interactions with neighboring groups may provide information about the local environment or may offer important reproductive opportunities. Considering the potential fitness consequences of intergroup interactions, particularly for territorial species that have long-term relationships with neighboring groups, we expect individuals will alter their behavior based on access to surrounding groups. We used a cooperatively breeding cichlid Neolamprologus pulcher to determine if individuals vary their response to a predator when neighbors were present versus absent. We found no difference in dominant behavior between neighbor present and neighbor absent treatments, but subordinates increased their defense against the predator when neighbors were present, particularly when the neighbor was unfamiliar. Subordinates may change their behavior when neighbors are present in order to signal to or cooperate with neighboring individuals but may also be responding to the change in intragroup dynamics that can result from the presence of neighboring conspecifics. This study illustrates the importance of considering the effect of neighboring groups on individual behavior, given that intergroup dynamics can influence behaviors that do not directly involve conspecific interactions.